The Influence of Store Atmosphere and Hedonic Consumption on Impulsive Buying Mediated by Positive Emotions - Wahyudi, Teguh Agus; Hasan, Irmayanti (Advances In Social Humanities Research, 2025)
This study seeks to investigate the impact of store atmosphere and hedonic consumption on impulsive purchase behavior among consumers at Hypermart Town Square in Malang City, mediated by happy emotions. The methodology employed is quantitative, utilizing an explanatory survey approach, wherein data is gathered via purposive sampling procedures involving a total of 80 respondents. This research investigates the correlation among store atmosphere, hedonic consumption, and happy emotions, along with their influence on impulsive purchasing behavior. The research findings indicate that store ambiance and hedonic consumption exert a positive and significant influence on impulsive purchasing behavior. Hedonic eating exerts a positive and considerable influence on happy feelings. Nevertheless, the retail ambiance does not substantially influence good emotions. Positive emotions exert a substantial and beneficial influence on impulsive purchasing behavior. The store atmosphere does not substantially impact impulsive purchasing through pleasant emotions, however hedonic consumption positively increases happy emotions, thereby affecting impulsive purchase.